Effects of aminoglycoside antibiotics on bound calcium and contraction in guinea-pig atria. - Lüllmann, H. (1985)
We studied the effect of three aminoglycoside antibiotics which have been shown to replace Ca from lipid monolayers on the superficially bound Ca of isolated beating left atria from guinea-pigs. The cellular Ca content was determined by means of 45Ca after having attained complete exchange. The antibiotics dibekacin, sisomicin, and gentamicin, all reduced the cellular Ca content by 10-20% in a dose-dependent manner. The loss of superficially bound Ca was accompanied by a decline of the contractile force by 40-90%. It is concluded that in isolated atrial muscle it is the amount of Ca bound to the outer surface of the cardiac plasmalemma, rather than the extracellular Ca2+ concentration, that determines contraction height.